Oxidation behaviour of neutron irradiated Be pebbles - N. Catarino; L.C. Alves; M. Dias; N.P. Barradas; S. van Til; M. Zmitko; E. Alves (Nuclear Materials and Energy, 2020)
Beryllium will be used as neutron multiplier material to increase the tritium breeding ratio in fusion reactors. The chemical reactivity of beryllium is a factor of major concern since the oxidation of beryllium at temperatures above 800°C can become an uncontrollable process. The present work presents a detailed study of chemical composition and reactivity of Be pebbles after exposure to neutron irradiation, up to 3000 appm He production, during the HIDOBE-01 campaign and their influence in the oxidation kinetics process. In order to get information on this reaction, samples were oxidized at 700°C under controlled air atmosphere (60% humidity) and with a mixture of 60% O2 + 40% N2. The chemical composition of the irradiated samples was studied using ion beam analysis and scanning electron microscopy. The observations revealed the presence of small flakes which are distributed in the surface, however no modifications in the pebbles shape after longer oxidation were observed. Ion beam elemental maps confirmed the presence of Be oxides distributed on the surface. Moreover, the width of the oxide layer increases with the annealing time, following a parabolic law.